Unpacking Multilingualism in Tourism Peripheries in Bali: Taking a Look into Private Shop-fronts - Dewianti Khazanah; Reni Kusumaningputri (k@ta: A Biannual Publication on the Study of Languange and Literature, 2021)
This article reports on the discussion of linguistic landscape in the course of tourism peripheries. The central aim is to unravel the salience and visibility of language practices manifested in the shop-fronts in Bali tourism peripherals. Drawing on Bourdieu’s language as social power (1983; 1993), presentation-of-self (Goffman, 1963; 1981), and good-reasons perspective (Boudon, 1990) we explore the language choices made by the local shop owners and the principles driving these choices. The findings conclude that English is the dominant language Bali tourism peripheries, and it is driven by the perceived power attributed to English and the economy benefits associated to English; the principle of presentation-of-self is not prioritized. We argue that local shop owners’ perception of targeted clients is the determining factor influencing it. Mandarin language need to be present more to cater the Chinese tourists for they constitute a big portion to the body of international tourists in Bali.